Empathy Crisis and Teacher Role Modeling: Adapting Bandura’s Theory for 21st-Century Character Education - Arum Nurul Aripin; Nanda Dwisetya; Viorrie Fitrah Azahra; Sitti Chadidjah (Islamic Journal of Education, 2025)
The digital transformation in the 21st century has triggered disruptions in social interactions, leading to a decline in empathy and a character crisis among Generation Z students. This article aims to examine the relevance of Albert Bandura's Social Learning Theory in mitigating the negative impacts of digital isolation and optimizing the formation of prosocial behavior. Employing a qualitative approach, this study analyzes the principles of observation, imitation, and modeling within the context of contemporary character education, particularly through the Mentor Life Learning framework at the primary school level. The analysis reveals that overreliance on gadgets without collaborative management fosters individualistic attitudes that threaten the humanizing essence of education. Therefore, the application of Bandura's theory requires educators to transform into "digital models" and facilitators who consistently demonstrate ethical and moral values in both physical and virtual spaces. The utilization of educational technology must be integrated with meaningful social interactions and the inculcation of Islamic values. This study concludes that the synergy between prosocial modeling through digital media and the real-world environment, supported by multi-stakeholder collaboration, is essential to equip students with self-regulation and a robust spiritual foundation to navigate the moral complexities of the cyber era